Project of historical linguistics of slavic studies of 1958 - Nedashkovsky, Leonard Fyodorovich (2022)
The article explores the paradoxes of methodology and political contexts of the project of historical linguistics of Slavic studies, which was officially declared during the IVth International Congress of Slavists (Moscow, 1958). The authors explore this significant project of historical linguistics from the point of view of intellectual history - through the problem of formation of ideas of researchers about the subject, method, and meta-language of Slavic studies, which has proved to be essential in the study of the history of this discipline. Semiotic analysis of the whole body of sources as a single text of ideology is utilized to attain the aim of the study. The project of historical linguistics of Slavistics (1958) is a fact of the history of discipline and ideology that reveals the relationship between the methodology of research and the practices of power and global projects to build national identity.